Start-up Business Plan in Chinese Race Funeral Services Industry: Eternal Life Care - Wong Chin Khang; Ahmad, Abd Razak (Research in Management of Technology and Business, 2023)
The funeral industry catering to the Chinese race in Malaysia has witnessed significant development, driven by cultural traditions and the growing demand for culturally appropriate funeral services. This has led to the emergence of specialized funeral service providers offering tailored offerings to meet the unique needs of the Chinese community in Malaysia.The purpose of this business plan is prepare for a start-up company which plan involve in funeral services industry. The primary objective of Eternal Life Care is to establish itself as a leading funeral services provider, with a specific focus on serving the Chinese community residing in the Johor Bahru area. The business plan for Eternal Life Care is supported by a strong viability assessment. The SWOT analysis highlights strengths such as a skilled team and flexible pricing, while the BMC identifies target customer segments and key activities. Marketing strategies emphasize cultural sensitivity, while operations focus on fast and round-the-clock service. Financial analysis emphasizes budgeting and resource allocation. Overall, the plan demonstrates a strong understanding of the market, differentiation from competitors, efficient operations, and strategic financial planning.